2022
DOI: 10.1039/d1ma00861g
|View full text |Cite
|
Sign up to set email alerts
|

Dual-functional inorganic CuSCN for efficient hole extraction and moisture sealing of MAPbI3 perovskite solar cells

Abstract: Most high-performing organic-inorganic hybrid perovskite solar cells (PSC) are fabricated using expensive organic hole-transporting materials (HTM). The poor moisture- and thermal-stability of organic HTM is a significant factor contributing to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Over the years, perovskite materials sandwiched between several charge transport layers like electron transport layers (ETLs) and HTLs, as well as front and back metal contacts. Currently, titanium dioxide (TiO 2 ) is widely considered to be the preferred ETL for PSCs when compared to other metal oxides. This phenomenon can be attributed to the favorable alignment between the conduction band of the material and the perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, perovskite materials sandwiched between several charge transport layers like electron transport layers (ETLs) and HTLs, as well as front and back metal contacts. Currently, titanium dioxide (TiO 2 ) is widely considered to be the preferred ETL for PSCs when compared to other metal oxides. This phenomenon can be attributed to the favorable alignment between the conduction band of the material and the perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…The double-graded PSC offers the maximum value of PCE of 24.10%, as shown in Figure 15. The current work is offering higher value of efficiency than the previous experimental result by Krishna et al, 37 and Huang et al 27 Also,the output value is also offering higher than the previous value of Hossain et al 67 The detailed comparison of the PV parameters is shown in the Tabular form in Table 3.…”
Section: The Impact Of Temperature On Both the Devicesmentioning
confidence: 48%
“…To deal with this, many researchers proposed a lead-iodide-based perovskite material, i.e., MAPbI 3 , which can provide excellent performance parameters. In a study, a device configuration FTO/SnO 2 /MAPbI 3 /CuSCN/Au achieved a PCE of 26.74% by Raoui et al While the experimental work by Krishna et al estimated a PCE of nearly 10.1% using the MAPbI 3 as the absorber layer and CuSCN as the HTL . Another modeling and simulation study by Azri et al on a single junction PSC with MAPbI 3 , ZnO, and CuSCN as the absorber, ETL, and HTL materials, respectively, resulted in a PCE of 25.02% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-deposited films were subsequently annealed on a hotplate at 110 °C for 15 min. Copper (I) thiocyanate (CuSCN) was dissolved in diethyl sulfide at a concentration of 35 mg/ml and then spin-coated onto the CsFA film at 2500 rpm for 40 s [8]. Finally, the device was completed by laminating a carbon electrode onto the CuSCN layer at 50 °C [9].…”
Section: Preparation Of Solar Cell Devicesmentioning
confidence: 99%